2016
DOI: 10.3389/fnhum.2015.00691
|View full text |Cite
|
Sign up to set email alerts
|

Haptically Guided Grasping. fMRI Shows Right-Hemisphere Parietal Stimulus Encoding, and Bilateral Dorso-Ventral Parietal Gradients of Object- and Action-Related Processing during Grasp Execution

Abstract: The neural bases of haptically-guided grasp planning and execution are largely unknown, especially for stimuli having no visual representations. Therefore, we used functional magnetic resonance imaging (fMRI) to monitor brain activity during haptic exploration of novel 3D complex objects, subsequent grasp planning, and the execution of the pre-planned grasps. Haptic object exploration, involving extraction of shape, orientation, and length of the to-be-grasped targets, was associated with the fronto-parietal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 88 publications
(173 reference statements)
2
20
0
Order By: Relevance
“…Consistent with our earlier study (Marangon, Kubiak, & Kroliczak, 2016), signal modulations in the angular gyri (AG), bilateral ventral PreCun, and mid-to-posterior middle and superior temporal gyri (mpMTG/STG) were revealed. The pattern, illustrated in Supplementary Figure 1A, results from greater inhibition of these areas for the more difficult task of planning grasps of tools.…”
Section: Planning Grasps Of Control Objects Versus Grasps Of Tools Wisupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our earlier study (Marangon, Kubiak, & Kroliczak, 2016), signal modulations in the angular gyri (AG), bilateral ventral PreCun, and mid-to-posterior middle and superior temporal gyri (mpMTG/STG) were revealed. The pattern, illustrated in Supplementary Figure 1A, results from greater inhibition of these areas for the more difficult task of planning grasps of tools.…”
Section: Planning Grasps Of Control Objects Versus Grasps Of Tools Wisupporting
confidence: 90%
“…The inverse contrast between pantomimed tool use and planning functional grasp revealed bilateral modulations in AG, vPreCun, mpMTG/STG, SI-MI, and dorsal lateral/medial prefrontal cortices. In our earlier study (Marangon et al, 2016), such a network was revealed for an easier manual task. Figure 4B also demonstrates that pantomime tool use invokes left aSMG/aIPS, right SI and Fig.…”
Section: Hand-independent Network For Planning Functional Grasps Andmentioning
confidence: 88%
“…Briefly, compared with the passive condition, cortical oscillations in the 6-24 Hz range were more synchronized from 0-175 ms within the somatosensory and parietal cortices during haptic exploration. These outcomes are aligned with prior functional MRI and EEG studies that have connected activity in these cortical regions with object localization during a haptic task (Reed et al 2005;Neuper et al 2006;Marangon et al 2015). Conversely, the sharp decreases seen in alpha (8-16 Hz) and beta (18-26 Hz) activity were notably stronger and centralized to the somatosensory cortices during the passive stimulation condition.…”
Section: Discussionsupporting
confidence: 79%
“…; Marangon et al . ). Conversely, the sharp decreases seen in alpha (8–16 Hz) and beta (18–26 Hz) activity were notably stronger and centralized to the somatosensory cortices during the passive stimulation condition.…”
Section: Discussionmentioning
confidence: 97%
“…Besides somatosensory areas, we expected to observe training-induced changes within multisensory cortical regions known to be involved in tactile recognition: the fusiform gyrus/lateral occipital cortex and associative parietal areas (Amedi et al, 2001 , 2002 ; Sadato et al, 2002 ; Kassuba et al, 2011 ; Kim and Zatorre, 2011 ; Marangon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%